Design, synthesis, and evaluation of α-galactopyranosylceramide mimics promoting Th2 cytokines production. Issue 11 (1st June 2019) - Hu, Liyan; Zhao, Chuanfang; Ma, Juan; Jing, Yang; Du, Yuguo
Graphical abstract: Two α-GalCer analogues were newly designed with the help of docking calculation and efficiently synthesized taking advantages of inverse glycosylation procedure. The prepared compounds exhibited good activity in stimulating mouse iNKT cells in vivo with a significant Th2 biasing immune response. Abstract: The binding properties of CD1d/glycolipid/TCR, glycolipid/TCR interactions in particular, have been investigated using docking computation. Accordingly, efficient modification on C-6′ of galactose head was recommended in this report to favor the production of Th2 cytokines. The designed glycolipids have been successfully prepared taking advantages of inverse glycosylation procedure, and their abilities to stimulate mouse iNKT cells in vivo have been tested. Compound 9, having p -hydroxyphenylpropionyl amide group on C-6′, presented the best result with respect to the selectivity and quantity on Th2-type cytokine IL-4. We found that the increased glycolipid/TCR interaction might be critical in designing new substrate with Th2-biased cytokine production.